The Effect of Smartboard Media on Students’ Arabic Learning Motivation of MTsN 2 Malang - M Sholih Salimul Uqba; Munirul Abidin; Hakiki Rikza Irnaini Al Badri (al-Afkar, Journal For Islamic Studies, 2025)
Efforts to increase student motivation or interest in learning can be done by using learning media, and what is still rarely used is smartboard. This study aims to determine the effect of using smartboard media on motivation to learn Arabic. This research is a descriptive quantitative research. The population in this study were students of SKS class MTsN 2 Malang, totaling 25 students. The data were processed using descriptive statistics with SPSS software and simple linear regression test. Based on hypothesis testing, the Sig. 0,003 < 0,05. Thus it can be concluded that Ha is accepted, namely there is an “effect of using smartboard media on students' Arabic learning motivation”. The results of this study inform that there is a significant influence between smartboard learning media on student learning motivation, especially in learning Arabic.